Clinicians’ Perspectives on Self-Harm in Pakistan: A Qualitative Study - Tayyeba Kiran; Nasim Chaudhry; Penny Bee; Sehrish Tofique; Sana Farooque; Afshan Qureshi; Anna K. Taylor; Nusrat Husain; Carolyn A. Chew-Graham (Frontiers in Psychiatry, 2021)
Background: Suicide is a serious public health problem, ranked amongst the leading causes of death worldwide. There are no official data on self-harm and suicide in Pakistan; both are illegal acts, and are socially and religiously condemned. This study explored the views of clinicians, including general practitioners (GPs) and hospital physicians (HPs) on self-harm, about their management of people who self-harm and what interventions might be appropriate in Pakistan.Methods: This qualitative study, generating data using semi-structured interviews, was nested within a Randomized Controlled Trial (RCT) of a psychosocial intervention for people following self-harm. Clinicians (n = 18) with experience of treating people who self-harm were recruited from public hospitals and general practices.Results: Face-to-face interviews were conducted in Urdu and digitally recorded with consent, transcribed and translated into English. Transcripts were checked for cultural and interpretive interpretations by the research team, then analyzed thematically using the principles of constant comparison. The following themes will be presented: encountering people with self-harming behaviors; challenges encountered in managing people who self-harm; barriers to accessing care, and what ideal care might look like. Participants identified their lack of training and expertise in the management of people with self-harm behavior.Conclusions: This is the first study to explore clinicians’ perspectives on self-harm in Pakistan. The study highlighted the need for training for doctors in the identification and management of mental health problems, including the management of people who self-harm.